Dodgeball: Inadvertently teaching oppression in physical and health education. (February 2021) - Butler, Joy; Burns, David P; Robson, Claire
Though students can learn a great deal about ethics as they play sport, the authors of this article ask what, exactly, they learn from playing dodgeball. As they look beyond the usual arguments offered for and against the teaching of the game, they view it through three ethical lenses: the ethic of care, the ethic of anti-oppressive education, and the ethics of virtue. They conclude that in terms of modelling, confirming, and practising caring behaviours, or offering opportunities to discuss and process what might be considered fair, dodgeball can be considered miseducative. They further argue that the hidden curriculum of dodgeball reinforces the five faces of oppression defined by the feminist theorist Iris Young as marginalization, powerlessness, and the helplessness of those perceived as weaker individuals through the exercise of violence and dominance by those who are considered more powerful. They conclude that the playing of dodgeball habituates the practice of aggression and fails to contribute positively to an ethical education.